2020
DOI: 10.1038/s41422-020-0317-6
|View full text |Cite|
|
Sign up to set email alerts
|

N6-methyladenine is incorporated into mammalian genome by DNA polymerase

Abstract: Dear Editor, DNA N 6-methyladenine (6mA), one of the most prevalent epigenetic base modifications in prokaryotes, 1 is recently found in multicellular eukaryotes. 2-8 This nucleobase may have epigenetic roles in regulation of retrotransposons, chromatin organization, and so on. 2-8 However, both our group 9 and Greer's group 10 noticed that eukaryotic DNA is easily contaminated with a minute of bacterial DNA, which carries overwhelmingly abundant 6mA (~2% 6mA/dA). 1 This brings great challenges for accurate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 15 publications
7
69
0
Order By: Relevance
“…Despite that ALKBH1 has recently been reported as a 6mA demethylase (Xiao et al, 2018;Xie et al, 2018), which is by far the only one identified in human, we did not observe discernible difference in the 6mA levels in hESCs, hMSCs or hVSMCs caused by ALKBH1 deficiency, consistent with the recent report that ALKBH1 fails to eliminate 6mA in mESCs or HEK293T cells (Liu et al, 2020). Given that two studies have shown that ALKBH1 preferably demethylates 6mA on unpaired DNAs (Tian et al, 2020;Zhang et al, 2020a), our results imply that there might be few unpaired DNAs in the normally cultured hESCs, hMSCs and hVSMCs.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Despite that ALKBH1 has recently been reported as a 6mA demethylase (Xiao et al, 2018;Xie et al, 2018), which is by far the only one identified in human, we did not observe discernible difference in the 6mA levels in hESCs, hMSCs or hVSMCs caused by ALKBH1 deficiency, consistent with the recent report that ALKBH1 fails to eliminate 6mA in mESCs or HEK293T cells (Liu et al, 2020). Given that two studies have shown that ALKBH1 preferably demethylates 6mA on unpaired DNAs (Tian et al, 2020;Zhang et al, 2020a), our results imply that there might be few unpaired DNAs in the normally cultured hESCs, hMSCs and hVSMCs.…”
supporting
confidence: 86%
“…Another study reported 6mA as merely a false-positive signal likely caused by mycoplasma contamination and/or nonspecific antibodies (Douvlataniotis et al, 2020). While we and others performed experiments to exclude the possibilities of 6mA contaminations from cell culture or from the reagents used in LC-MS/ MS assay (Liu et al, 2020), proving the existence and primary origin of human genomic DNA 6mA is still a challenge in this field. With full consideration of these caveats, our study indicates that ALKBH1 is a key homeostatic regulator of human diploid adult stem cells and terminally differentiated cells.…”
Section: Cellmentioning
confidence: 85%
See 1 more Smart Citation
“…Other studies have failed to detect N6mA in several mouse tissues and mitochondrial DNA from human placenta ( 14 ), DNA isolated from mouse embryonic stem cells or brain and liver tissue ( 15 ) or cultured human cells ( 16 ). Nevertheless, more recent reports present evidence for low levels of N6mA in DNA from cultured human and mouse cells; however, that modified adenosine is incorporated (at least in part) by DNA polymerase using deoxy-N6mA converted from RNA-derived ribo-N6mA, via the nucleotide salvage pathway ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this makes it necessary to identify a 6mA position in the genome sites. Mammalian 6mA largely originates from the genomic incorporation mediated by DNA polymerase, while the methylase-generated 6mA in mice remains elusive [ 8 ].…”
Section: Introductionmentioning
confidence: 99%